1986
DOI: 10.1002/art.1780290306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warfarin sodium therapy on excretion of 4‐carboxy‐L‐glutamic acid in scleroderma, dermatomyositis, and myositis ossificans progressiva

Abstract: The effect of warfarin sodium on excretion of calcium, phosphorus, and 4-carboxy-L-glutamic acid (Gla) was studied in 5 patients with ectopic calcification (2 with scleroderma, 1 with dermatomyositis, and 2 with myositis ossificans progressiva). Warfarin reduced urinary excretion of Gila in all patients, but no changes in calcium and phosphorus excretion or in objective parameters of calcinosis were observed during 6-36 months of treatment. Two patients experienced hemorrhagic complications during therapy, emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The number of isolated cases reported that were treated empirically and no organized trial has highlighted the absence of an effective and codified treatment for CC. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The following agents have been prescribed: diltiazem, 11 aluminum hydroxide, 12 sodium thiosulfate, 13 colchicine, 14 edathamil, 15 intravenous immunoglobulins, 16 carbon-dioxide laser, 17 warfarin, 18 minocycline, 19 or bisphosphonates, 20-23 achieving variable efficacy and causing significant side effects. Excision of CC that are painful or a source of disability is sometimes proposed, but the topography (distal and periarticular site for SSC) and the extent of the lesions (CVI) can render surgical management difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The number of isolated cases reported that were treated empirically and no organized trial has highlighted the absence of an effective and codified treatment for CC. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The following agents have been prescribed: diltiazem, 11 aluminum hydroxide, 12 sodium thiosulfate, 13 colchicine, 14 edathamil, 15 intravenous immunoglobulins, 16 carbon-dioxide laser, 17 warfarin, 18 minocycline, 19 or bisphosphonates, 20-23 achieving variable efficacy and causing significant side effects. Excision of CC that are painful or a source of disability is sometimes proposed, but the topography (distal and periarticular site for SSC) and the extent of the lesions (CVI) can render surgical management difficult.…”
Section: Discussionmentioning
confidence: 99%
“…As the exact pathogenesis of FOP is not understood no standard treatment protocol capable of stopping progression of the disease exists. Several treatment modalities have been described (Moore et al , 1986; Bruni et al , 1990; Crofford et al , 1990) including calcitonin, non‐steroidal anti‐inflammatory drugs, isotretinoin, warfarin, and diphosphonates showing diverse results.…”
Section: Discussionmentioning
confidence: 99%